The Image of Syrian Refugees in the Lebanese Press: Case of Al-Akhbar Newspaper - El Zein, Hatem (Žurnalistikos tyrimai, 2021)
This paper investigates how Syrian refugees are portrayed in the Lebanese press, namely in Al-Akhbar Newspaper.Although there are existing studies that focus on the media representation of Syrian refugees, they allot significant attention to negative images of Syrian refugees presented by a number of Lebanese media outlets. In addition, there is a dearth of studies that scrutinise positive representation of Syrian refugees in the Lebanese press.Owing to these problems, this paper bridges the gap in the current literature through paying further attention to the positive media representation of Syrian refugees in the Lebanese press taking the case of Al-Akhbar Newspaper.In answering the question: how Al-Akhbar depicts Syrian refugees who fled to Lebanon, this paper analyses samples of articles published in Al-Akhbar to highlight the discourse of this Newspaper relating to Syrian refugees. The paper draws on qualitative analysis to arrive at its conclusion.The findings of the paper are significant because they reveal journalistic practices and agenda towards one of the serious issues in Lebanon which suffers from political turmoil and severe economic crisis. As this paper distinguishes between what it calls antagonist and protagonist discourses in reporting Syrian refugees in the Lebanese press, it recommends paying further attention to the protagonist discourse because it reflects good journalistic practice.